The Richness of Life - Stephen Jay Gould (Vintage, 2007)
There aren't many scientists famous enough in their lifetime to be canonized by the US Congress as one of America's 'living legends'. Yet few would have grudged this accolade to Stephen Jay Gould, whose writings on history - both of the natural world and of the study of the natural world - had made him a household name by the time of his death in 2002. A committed Darwinian and robust critic of creationist myths, he nevertheless made major revisions to orthodox Darwinian theory, from his concept of punctuated equilibrium to his insistence on the importance of chance in the history of life on earth. And in addition, his trenchant attacks on scientific racism and the pretensions of sociobiology still resonate, nearly three decades after they were first written. In The Richness of Life, Steven Rose and Paul McGarr have selected from across the full range of Gould's writing, including some of the most famous of his essays and extracts from his major books. An introduction by Steven Rose sets both the essays, and Gould's life, in context.